Comparative analysis of patients’ satisfaction level, hospitalized before and during the COVID-19 pandemic - Wójcik, Rena; Adam, Anna; Golonka, Ewa (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Measurement of the satisfaction level with health services is the most frequently used indicator, mainly because of its importance for determining the quality of the care offered. It is the key to succeed in achieving high-quality healthcare. The purpose of this study was to create a retrospective comparative analysis of the satisfaction level amongst patients hospitalized before and during the COVID-19 pandemic. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study covered a total of 966 patients in 19 hospital wards, in the fourth quarter of 2019 (before the pandemic) and in the second quarter of 2021 (during the pandemic) at the Masovian Specialist Hospital in Radom. The level of patient satisfaction was assessed based on the questionnaire prepared and approved by the Quality Assurance Team in the Masovian Specialist Hospital. The statistical analysis was carried out on the basis of the STATISTICA 10.1 program, using the Pearson’s chi square test, for the significance level at p<0.05. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The high level of satisfaction of patients staying in the hospital during the pandemic applied to the widely understood medical and nursing care as well as sanitary conditions in wards, especially the cleanness of rooms, bed linens and sanitary facilities. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The biggest dissatisfaction of hospitalized patients during the COVID-19 pandemic involved certain restrictions of visitations and using pastoral services.